Relationship between child abuse exposure and reported contact with child protection organizations: Results from the Canadian Community Health Survey. (August 2015) - Afifi, Tracie O.; MacMillan, Harriet L.; Taillieu, Tamara; Cheung, Kristene; Turner, Sarah; Tonmyr, Lil; Hovdestad, Wendy
Abstract: Much of what is known about child abuse in Canada has come from reported cases of child abuse and at-risk samples, which likely represent the most severe cases of child abuse in the country. The objective of the current study is to examine the prevalence of a broad range of child abuse experiences (physical abuse, sexual abuse, and exposure to IPV) and investigate how such experiences and sociodemographic variables are related to contact with child protection organizations in Canada using a representative general population sample. Data were drawn from the 2012 Canadian Community Health Survey: Mental Health collected from the 10 provinces using a multistage stratified cluster design ( n  = 23, 395; household response rate = 79.8%; aged 18 years and older). Physical abuse only (16.8%) was the most prevalent child abuse experience reported with the exposure to specific combinations of two or more types of child abuse ranging from 0.4% to 3.7%. Only 7.6% of the adult population with a history of child abuse reported having had contact with child protection organizations. Experiencing all three types of child abuse was associated with the greatest odds of contact with child protection organizations (AOR = 15.8; 95% CI = 10.1 to 24.6). Physical abuse only was associated with one of the lowest odds of contact with child protection organizations. Preventing child abuse is widely acknowledged as an important, but challenging public health goal. Strategies to increase reporting of child abuse may help to protect children and to connect families with necessary services. One obvious priority would be physical abuse.